A study on occurrence of backache and hearing loss among graduates of U.P. College of Dentistry with at least eight years of practice - Caparas, Ma. Joely
This study aims to determine whether hearing loss and backache are acquired by dentists through their years of practice. Dentists with at least eight (8) years of practice and graduating students of 1992 comprise the entire sample of this study. Fifteen dentists and fifteen students were chosen as subjects for hearing loss. Another group of twenty five students and twenty five dentists make up the sample for the study on backache. The subjects were selected on the basis of the questionnaires mailed to them. The questionnaires are composed of three parts. The first part sought background information. The second part were questions about backache and the third part were questions regarding the subject's ear. Several criteria for the screening of subjects prior to actual testing were set to be able to select the subjects to be tested for hearing loss and also to selected the sample for the study of backache. Actual tests for hearing loss were conducted to screened subjects using a pure tone audiometer. For backache, only the questionnaires were used to determine its existence. Results of the tests for hearing loss indicate normal hearing thresholds. This result suggests that there is no significant association between the occurrence of hearing loss and years of practice. Results of the questionnaires used for backache were tabulated, graphed and statistically analyzed. Statistical tools used were chi square test and point biserial correlation to determine the significance of these results. The results indicate that backpain can occur regardless of whether the subject is a dentist or a student, since most of the subjects experience backpain. It has also been found the age, years of practice, average chairside hours per week and average number of patients per week cannot be related to the presence or absence of backpain. Lastly, this study also established that there is no significant difference between working positions factors such as incidence, location and duration of backpain.